Epistemology of Musthafa Umar’s Interpretation on the Kajian Tafsir Al-Ma’rifah YouTube Channel - Siti Zakiah, Ade Rosi; Thoriquddin, Moh. (Millati: Journal of Islamic Studies and Humanities, 2022)
A review of the epistemology of the audiovisual interpretation of the “Kajian Tafsir Al-Ma’rifah” YouTube channel delivered by Musthafa Umar is important to find out the source of interpretation, the method of interpretation, and the benchmark for the validity of his interpretation. Considering that a work of interpretation cannot be separated from various tendencies of commentators, whether it is caused by socio-cultural conditions in their environment, political influences, science, the context in which the interpretation was born, and others. Thus, studying the epistemology of interpretation becomes an urgent scientific problem to be addressed to know an interpretation. This paper is to significantly reveal the epistemology of Musthafa Umar’s thoughts in the process of interpretation on YouTube. Based on a study of the epistemology of audiovisual interpretation delivered on the “Kajian Tafsir Al-Ma’rifah” YouTube channel, it was found that Musthafa’s interpretation belongs to the category of bil ma’tsur and bil ra’yi interpretations. When interpreting Al Qur’an, he combines the tahlili (analytical) method and the maudhu’i (thematic) method. His interpretation is correct because it follows the coherence, correspondence, and pragmatic theory of truth.